The Implementation of Classroom Management during Teaching Practice in Micro-Teaching Class by English Department Students - Febryana, Nadya Ayu Nur; Addinna, Ainul (Journal of English Language Teaching, 2024)
Micro-teaching is one of the courses required for education students at the university. In Micro-teaching class, students practice teaching in a controlled classroom setting. In practice, students also learn how to manage the classroom. This research aims to examine the implementation of classroom management by students based on the six main areas proposed by Scrivener namely activity, grouping & seating, authority, critical moments, tools & technique, and working with people. Two English department students from K1-2021 who present two similar lesson plans will be observed, and the results will be processed using qualitative descriptive techniques. It can be concluded that out of the six areas, there are two areas that can be further explored: the activity area and the critical moment area.